PENERAPAN GOOD MANUFACTURING PRACTICES (GMP) PADA USAHA PEMBUATAN BAWANG GORENG (STUDI KASUS PADA IKM JAKARTA PUSAT) - Meilan Agustin (Fakultas Teknik Universitas Borobudur, 2020)
Bawang Goreng “Delisi” is a Micro and Medium Small Business that has spezialition on fried onin packaging. On this day the product already available in around 300 modern market on Jabodetabek and others big city in Indonesia. As a food producer, the safety and health of what customer consumption is a must. Endanger foods could be cause poisoning. A lot of thing could be caused this unsafety, among others such as nature process like oxidation or decay, pollution like heavy metal, pesticide or bacteria. Badan Pengawas Obat dan Makanan (BPOM) has set a regulation about how to make a good product for home made or usually called Good Manufacturing Practices (GMP) that will keep the quality of food safe and worthy to consumption. The result of analysis said, from 8 rated variable, 5 variable get “Good” score and 3 variable get “Sufficient” scoreKey Words: Good Manufacturing Practices (GMP), HACCP, Food Industry.